2021
DOI: 10.1001/jamadermatol.2021.0009
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Atopic Dermatitis and Educational Attainment in Denmark

Abstract: Key Points Question Is atopic dermatitis (AD) associated with lower educational attainment? Findings This nationwide matched cohort study of 61 153 Danish children found evidence of reduced attainment of lower and upper secondary education in 5927 children with a hospital diagnosis of AD compared with 55 226 matched children from the general population; however, absolute differences were less than 3.5%. Estimates were less pronounced in a secondary analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 29 publications
2
18
1
Order By: Relevance
“…Ultimately, it is important to understand whether an AD diagnosis warrants additional screening and/or resources beyond the general interventions designed for children at risk for poor educational outcomes. Both studies by Schmidt et al 5 and Wan et al 6 in this issue showed that associations were independent of other atopic disease (ie, asthma and rhinitis) and other neuropsychiatric conditions (ie, attention-deficit/hyperactivity disorder, depression/anxiety, and epilepsy). This observation suggests that screening children with AD may be a good way to identify those who may benefit from educational interventions, but more work is needed.…”
mentioning
confidence: 88%
See 3 more Smart Citations
“…Ultimately, it is important to understand whether an AD diagnosis warrants additional screening and/or resources beyond the general interventions designed for children at risk for poor educational outcomes. Both studies by Schmidt et al 5 and Wan et al 6 in this issue showed that associations were independent of other atopic disease (ie, asthma and rhinitis) and other neuropsychiatric conditions (ie, attention-deficit/hyperactivity disorder, depression/anxiety, and epilepsy). This observation suggests that screening children with AD may be a good way to identify those who may benefit from educational interventions, but more work is needed.…”
mentioning
confidence: 88%
“…4 Two new studies in this issue of JAMA Dermatology address this research gap. 5,6 Their results suggest an association among AD, learning, and education, yet a lot remains to be understood about this topic.The study by Schmidt et al 5 aimed to evaluate the association of AD with educational attainment over the past 4 decades in Denmark. Using nationwide data on children with a hospital diagnosis of AD who were matched to control participants from the general population, the authors found that those with AD had a 50% (risk ratio, 1.50; 95% CI, 1.26-1.78) greater likelihood of not completing lower secondary education (equivalent to junior high graduation in the US) and a 16% (risk ratio, 1.16; 95% CI, 1.09-1.18) greater likelihood of not completing upper secondary education (equivalent to high school graduation in the US), but no statistically significant difference in higher educational attainment was found.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7][8] Most research into the impact of chronic health conditions on education focuses on quantitative outcomes of school attendance and attainment and concludes that outcomes are negatively impacted by a chronic health condition to varying degrees. [9][10][11][12][13][14][15][16][17] For example, studies conducted in childhood epilepsy, diabetes and asthma all showed relative deficits in educational attendance or attainment. [10][11][12] However, attainment and attendance do not tell us how school life is experienced by young people with chronic conditions.…”
Section: Introductionmentioning
confidence: 99%